An Analysis upon Various Challenges and Opportunities of Mother Tongue Based Schooling for Improving Educational Quality: Exploring the Benefits and Challenges of Mother Tongue Based Schooling (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education fully develops human potentials, especially the cognitive power and in any program taking the cognitive abilities of the human being into consideration language is a necessary instrument of thought. Language has a central position in all the situations involving human learning. But a significant proportion of children in many developing countries, enter school not speaking the language of the classroom. Whereas to effectively teach around 221 million children worldwide speaking a different language at home from the one used as medium of instruction in schools, there is a need to teach them first in their home language while gradually introducing the national or official language or foreign language. Education when imparted in foreign language or any language which is not spoken at the home of pupils or in their surrounding atmosphere causes difficulties in learning and understanding, leading to their failure in courses or drop out from the schools, which is a big loss to a country, nation and even to humanity at large. All the international forums like UNESCO, the World Bank, World Declaration on ‘Education for All’ (EFA), the UNO General Assembly’s Convention on the Child’s Rights etc has stressed to educate children at least at primary level using mother tongue as medium of instruction. Because researches have shown that mother tongue-based schooling significantly improves learning. While there are many factors involved in delivering quality basic education, language is clearly the key to communication and understanding in the classroom. Many developing countries, are characterized societal multilingualism; yet continue to allow a single foreign language to dominate the education sector. However, the issues of mother tongues should be underlined as we look for quality of education in the grass root level. Therefore, this paper highlights important issues in mother tongue education such as arguments in the using of mother tongue for classroom instruction, various countries experiences in the benefits of mother tongue based education and the role of mother tongue education in maintaining quality of education. Eventually, it forwards recommendations which should be considered in further actions.